Knowledge, Expertise, and Experience on Employee Performance at PDAM Tirta Siak Pekanbaru City - Andi; Jufrianto; Tanjung, Amries Rusli; Komardi, Dadi; Purnama, Intan (First Ciera Publisher, 2023)
The purpose of this study was to determine the effect of knowledge, expertise, and experience on employee performance. This research was conducted at PT. PDAM Tirta Siak Pekanbaru City. The population is the total number of employees at PT. PDAM Tirta Siak Pekanbaru City, namely 119 people. Then the sample in this study is the entire population in this study, amounting to 119 people. The technique of determining the sample using the census method. Data analysis using multiple linear regression. The results of the study explain that the knowledge variable, expertise variable, and experience variable have a positive and significant influence on employee performance variables at PDAM Tirta Siak Pekanbaru City.